Interaction between SH0 guided waves and tilted surface-breaking cracks in plates - Combaniere,J; Cawley,P; McAughey,K; Giese,J (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control, 2019)
The interaction between SH0 guided waves and simple defects is well understood and documented, and the SH0 and related torsional guided waves are commonly used in inspection. However, tilted and branching cracks, for which vertical notches are a poor approximation, are found in some environments, particularly when pipes are buried in alkaline soils. This paper studies the interaction between SH0 guided waves and tilted, surface-breaking cracks, investigating the effect of the tilt and depth of the defect. The incident wave interacts with the tilted crack to generate a transmitted wave, a reflected wave and a wave trapped below the crack. It is shown that the direction of the tilt of the crack relative to the incident wave direction does not affect the scattering behaviour. Additionally, the axial extent of the crack plays a major role in the reflectivity of the crack, leading to transmission nulls in some configurations. These transmission nulls appear for all crack depths, the frequency range over which the transmission is significantly reduced increasing with crack depth. This behaviour is shown to be analogous to the acoustic energy flow in a duct when a Helmholtz resonator is introduced. The null is not seen above the SH1 cut-off as the propagating signals are no longer mono-modal. The existence of a transmission null and corresponding reflection maximum is promising for the detection of small defects and measurement of the frequency at which the null occurs will assist with defect characterisation. Experimental validations of the key results are presented.